2012
DOI: 10.1371/journal.pone.0037825
|View full text |Cite
|
Sign up to set email alerts
|

Aetiologies of Central Nervous System Infection in Viet Nam: A Prospective Provincial Hospital-Based Descriptive Surveillance Study

Abstract: BackgroundInfectious diseases of the central nervous system (CNS) remain common and life-threatening, especially in developing countries. Knowledge of the aetiological agents responsible for these infections is essential to guide empiric therapy and develop a rational public health policy. To date most data has come from patients admitted to tertiary referral hospitals in Asia and there is limited aetiological data at the provincial hospital level where most patients are seen.MethodsWe conducted a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
71
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 55 publications
10
71
5
1
Order By: Relevance
“…This result is much higher than several studies noted that the incidence of intracranial postneurosurgical infection have been ranged between 0.4% to 7.7% [4,5,6,7]. The profile of CSF isolates in this study showed that certain bacteria species were the predominant cause of CNS infection and was similar to other studies [1,2,8,10] . Coagulase negative Staphylococci was responsible for 39.4 of CSF positive culture, which was similar to a recent Iranian study [16].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This result is much higher than several studies noted that the incidence of intracranial postneurosurgical infection have been ranged between 0.4% to 7.7% [4,5,6,7]. The profile of CSF isolates in this study showed that certain bacteria species were the predominant cause of CNS infection and was similar to other studies [1,2,8,10] . Coagulase negative Staphylococci was responsible for 39.4 of CSF positive culture, which was similar to a recent Iranian study [16].…”
Section: Discussionsupporting
confidence: 83%
“…CNS infections are life-threatening and significant causes of morbidity and mortality, especially in developing countries [1,2]. Bacterial infections have been known as the most common cause of the CNS infections, meanwhile fungi and mycobacteria are also frequently reported [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the bacterial causes of meningitis infections in developing countries is difficult due to the limited number of bacteriological culture facilities and lack of BACTEC automated culture system (15). In the present study, we used the BACTEC culture system to improve the yield of clinically significant isolates from normally sterile body fluids and reduce the time required for microorganism detection (16).…”
Section: Discussionmentioning
confidence: 99%
“…CSF samples were not available from all the patients. Other AES agents, including bacteria and parasites, have been suggested as causative agents of AES for patients negative for antiflavivirus antibodies (2,(14)(15)(16)(17). In Vietnam, anti-JEV IgM positivity among AES patients varies from 17 to 71 (9).…”
Section: Discussionmentioning
confidence: 99%